RNA polymerase activity in bovine spermatozoa (The Rockefeller University Press, 1977)
Washed mature spermatozoa from bulls incorporate ribonucleoside triphosphates into RNA using an endogenous template. Maximum incorporation was observed at 31 degrees C in the presence of MgCl2, all four ribonucleoside triphosphates, beta-mercaptoethanol, and glycine sodium hydroxide buffer at pH 9.0. The amount of synthesis was linearly dependent upon the concentration of spermatozoa and continued for at least 4 h. Digestion studies revealed the RNA to be present in a protected (intracellular?) location in the spermatozoa. The RNA synthesis was inhibited by ethidium bromide, rifampicin, acriflavine, actinomycin D, and caffeine, but not by alpha-amanitine or rifamycin SV. Fractionation of the spermatozoa by sonication and separation of the heads and tails by centrifugation through a discontinuous gradient revealed that more than half of the total RNA polymerase activity was associated with the tail fraction.